Spectacular Disappearances - Fawcett, Julia H. (University of Michigan Press, 2016)
How can people in the spotlight control their self-representations when the whole world seems to be watching? The question is familiar, but not new. Julia Fawcett examines the stages, pages, and streets of eighteenth-century London as England's first modern celebrities performed their own strange and spectacular self-representations. They include the enormous wig that actor Colley Cibber donned in his comic role as Lord Foppington--and that later reappeared on the head of Cibber's cross-dressing daughter, Charlotte Charke. They include the black page of Tristram Shandy, a memorial to the parson Yorick (and author Laurence Sterne), a page so full of ink that it cannot be read. And they include the puffs and prologues that David Garrick used to heighten his publicity while protecting his privacy; the epistolary autobiography, modeled on the sentimental novel, of Garrick's protégée George Anne Bellamy; and the elliptical poems and portraits of the poet, actress, and royal courtesan Mary Robinson, a.k.a. Perdita. Linking all of these representations is a quality that Fawcett terms "over-expression," the unique quality that allows celebrities to meet their spectators' demands for disclosure without giving themselves away. Like a spotlight so brilliant it is blinding, these exaggerated but illegible self-representations suggest a new way of understanding some of the key aspects of celebrity culture, both in the eighteenth century and today. They also challenge divides between theatrical character and novelistic character in eighteenth-century studies, or between performance studies and literary studies today. The book provides an indispensable history for scholars and students in celebrity studies, performance studies, and autobiography-and for anyone curious about the origins of the eighteenth-century self.